Reverse engineering the mind : consciously acting machines and accelerated evolution - Neukart, Florian (Springer, 2017)
Florian Neukart describes methods for interpreting signals in the human brain in combination with state of the art AI, allowing for the creation of artificial conscious entities (ACE). Key methods are to establish a symbiotic relationship between a biological brain, sensors, AI and quantum hard- and software, resulting in solutions for the continuous consciousness-problem as well as other state of the art problems. The research conducted by the author attracts considerable attention, as there is a deep urge for people to understand what advanced technology means in terms of the future of mankind. This work marks the beginning of a journey - the journey towards machines with conscious action and artificially accelerated human evolution. Contents Strong AI by Fusing the Human Brain with Technology Continuous Consciousness by Artificially Extending the Mind Target Groups Lecturers and students in the fields of artificial intelligence, quantum physics/computing, psychology, neuroscience and computational neuroscience Practitioners with interest in the future of AI, working for car manufacturers, software companies or robotics companies About the Author Dr. Florian Neukart worked as a data scientist for one of the largest mobility providers worldwide and was responsible for technology and research in one of their applied research departments. He still works there as a principal data scientist and lecturer and researcher in the field of quantum computer science in both academia and industry.
Keywords: Conscious automata.; Neurosciences.; Artificial intelligence.; Neuropsychology.; elektronické knihy; electronic books